Peran Teknologi Informasi dalam Meningkatkan Efesiensi Oprasional pada Perusahaan E- Commerce - Putri Ainayah Tazkiyah; Nibi Nazwa Quinita Tanjung; Devita Azwi Nurrahma; Albi Wahyu Ramadhan; Siti Suaibah Nasution (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
This study aims to analyze the strategic role of Information Technology (IT) in improving operational efficiency within e-commerce companies in Indonesia. A literature review approach was employed by examining various scholarly sources, including accredited national journals and relevant books. The findings indicate that the implementation of IT such as Enterprise Resource Planning (ERP) systems, Big Data Analytics, and Cloud Computing significantly accelerates business processes, reduces operational costs, and enhances data accuracy and service quality. E-commerce companies that integrate IT into their operations are shown to adapt more effectively to market dynamics and consumer preferences. The study concludes that the use of IT is not merely a supporting tool, but a key factor in creating competitive advantage. The implications of this research offer insights for e-commerce industry players and policymakers to continuously promote digital innovation in pursuit of efficiency and business sustainability.